2018
DOI: 10.1111/pirs.12302
|View full text |Cite
|
Sign up to set email alerts
|

The demand for gambling in Italian regions and its distributional consequences

Abstract: In recent years, the Italian gambling market has exploded, leading Italy to become\ud the largest European gambling market and the fourth largest worldwide but the literature on\ud the topic is still limited. This study analyses gambling demand across Italian regions in order\ud to detect how the socio-economic status of a region impacts the demand for different games.\ud The results reveal that the consumption of each game is unevenly distributed across the northern\ud and southern regions and that gambling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…These differences have also affected—and still affect—gambling habits, which are stronger in the South of Italy. Specifically, gambling has gained more social acceptance in Southern regions, where gambling is more frequent among both the whole population and adolescents (e.g., Bastiani et al, 2013; Gandullia & Leporatti, 2018; Talamo & Manuguerra, 2016). Hence, the opportunity cost attached to deceive parents about gambling is more likely to be lower in the South than in the rest of the country.…”
Section: Discussionmentioning
confidence: 99%
“…These differences have also affected—and still affect—gambling habits, which are stronger in the South of Italy. Specifically, gambling has gained more social acceptance in Southern regions, where gambling is more frequent among both the whole population and adolescents (e.g., Bastiani et al, 2013; Gandullia & Leporatti, 2018; Talamo & Manuguerra, 2016). Hence, the opportunity cost attached to deceive parents about gambling is more likely to be lower in the South than in the rest of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Perez and Humphreys (2013, Table 3) report the results of 16 empirical studies, the majority of which found that lotteries are regressive, assessed either by estimating the income elasticity of demand, the Suits index (Suits, 1977), or both. The regional dimension of the distributional impact of gambling has also been assessed using Canadian data (Kitchen and Powells, 1991) and more recently for Italian regions (Gandullia and Leporatti, 2018). In his analysis of the U.K. National Lottery, Wheeler (2018) estimates a range of values for the income elasticity of demand, from -1.4 to -0.7, suggesting that the lottery is an inferior good.…”
Section: Background Literaturementioning
confidence: 99%
“…The gambling industry is not a singular entity, but rather a multifaceted sector that involves complex systems of production, distribution, and retail (Gandullia and Leporatti, 2018). Geographers have explored the role of neoliberal capitalism, deregulation, liberalised policy environments, and urban development in promoting casino gambling as an economic driver (Brenner and Theodore, 2002; Peck, 2017; Rogers and Gibson, 2021; Wilson, 2003; Young et al, 2009).…”
Section: Introductionmentioning
confidence: 99%